Fatigue strength of sharp V-notched specimens made of ductile cast iron. (December 2017) - Berto, F.; Ferro, P.; Salavati, H.
Abstract: In the present, the high cycle fatigue strength of notched ductile cast iron is investigated. Experimental tests under axial loading, has been carried out on sharp V-notched specimens taken from heavy section casting considering nominal load ratios ( R  = 0). All specimens, taken from a heavy section casting, are characterized by a notch tip radius less than 0.1 mm, a notch depth of 10 mm and a notch opening angle = 90°. In order to evaluate the influence of chunky graphite morphology on fatigue life, fatigue tests were carried out also on a second set of specimens without that microstructural defect. Metallurgical analyses were performed on all the samples and some important microstructural parameters (nodule count and nodularity rating, among others) were measured and compared. It was found that a mean content of 40% of chunky graphite in the microstructure (with respect to total graphite content) does not influence significantly the fatigue strength properties of the analysed cast iron. Highlights: Static and fatigue tests performed on ferritic ductile cast iron (EN-GJS-400) specimens weakened by a double sharp V notch The influence of degenerate graphite (chunky graphite, CHG) on fatigue strength of the analysed material was evaluated The fatigue life of both CHG-free and CHG-containing samples is dominated by the crack initiation period The variation in the fatigue life between the two kinds of samples is attributed to the different crack propagation mechanism